The perception of mothers coming from Primary Health Care on the Humanization of Childbirth care in a teaching hospital - Yi Wei, Chang; Rosa Gualda, Dulce Maria; Florentino Pereira da Silva, Lúcia Cristina; Melleiro, Marta Maria (O Mundo da Saúde, 2012)
The perception of users of health services has been widely discussed and taken into consideration in implementing health policies in order to meet their expectations and needs. The integration between different health services favors the articulation of the actions for promoting, preventing and recovering health, thus ensuring the flow and accessibility of patients to these institutions. In obstetrics, thanks to the movement toward humanization of childbirth care, this has been a fundamental assumption. Among the initiatives recommended for this purpose is contemplating the skin contact of mothers and babies after birth. The objective of this study was to know women’s experience related to skin contact with their babies at the time immediately following birth. This is an exploratory study with a qualitative analysis. It was conducted in a teaching hospital in Sao Paulo. Data were collected through interviews with the participation of 35 women who gave birth before and after the implementation of this practice. The perceptions reported by these women were: babies get peaceful when they feel the mother’s warmth and recognize her, there’s relief for the mother, she feels emotion, and it helps to create attachments between babies and mothers and reduces the suffering of parturition. The results provided valuable insights about the positive and negative aspects for the users with the implementation of the practice